AB1263 Higher prevalence of anti-citrullinated protein antibodies (ACPA) without impact on prognosis in patients with aggressive B-non-hodgkin lymphoma (DLCBL). (23rd January 2014) - Assmann, G.; Shihadeh, K.; Ong, M.F.; Ziepert, M.; Poeschel, V.; Pfreundschuh, M.
Abstract : Background: The complex processes of citrullination presents an ubiquitous pathophysiological procedure during inflammation. However, anti-citrullinated protein antibodies (ACPA) are highly specific for the rheumatoid arthritis (RA). In order to a variety of several autoimmune phenomenons during the course of lymphoma diseases the occurrence of autoantibodies like rheumatoid factors (RF) and antinuclear autoantibodies (ANA) has been reported. Objectives: Detecting the prevalence of anti-citrullinated protein antibodies (ACPA) in patients with DLCBL and its impact on prognosis including overall survival. Methods: We conducted a case control study analyzing 395 sera of patients DLCBL and of 249 healthy controls (HC) to compare the frequency of ACPA-positivity using the χ2-tests for 2×2 tables (with fisher correction as required). In addition, DLCBL patients were stratified into gender, age, stage of lymphoma disease, ESR, LDH elevation, ECOG performance status, and overall survival (analyzed by Mann-Whitney-test and Kaplan-Meyer-curve, respectively). Results: The A-CCP have been detected in the sera of 14 DLCBL patients (3.5%) more frequently than in the sera of HC (n=2, 0.8%, p=0.030). The subgroup analysis of female patients in both cohorts showed 4.4% ACPA positive DCBL patients and no HC (p=0.018). Data of DLCBL patients stratified into gender, age $<>$60y, stage of disease, performance status, ESR, LDH elevation, and overall survival (OS) show no differences between ACPA positive and negative patients (table ). However, there was a trend towards better 6-year OS for ACPA positive cohort (66.79% versus 60.26%). Conclusions: The patients with aggressive B-Non-Hodgkin lymphoma (DLCBL) showed more frequently anti-citrullinated protein antibodies (ACPA) compared to healthy controls. However, the ACPA could not been proved as a prognostic marker for DLCBL. Disclosure of Interest: None Declared